2010
DOI: 10.1002/jmri.22223
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of cerebral microbleeds with dual‐echo T2*‐weighted magnetic resonance imaging at 7.0 T

Abstract: Purpose: To assess the visualization of cerebral microbleeds with dual echo T2*-weighted imaging at 7.0 T magnetic resonance imaging (MRI). Materials and Methods:Ten consecutive participants (eight men, two women, mean age 54 6 12 years) with vascular disease or risk factors from the second manifestations of arterial disease (SMART) study were included. Dual-echo T2*-weighted scans (echo time: 2.5/15.0 msec) were made for all participants at 7.0 T MRI. The number of visible microbleeds and the diameter of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…The use of the TE1 image at 7T is helpful to distinguish microbleeds from deoxyhemoglobin in veins and ferritin in the basal ganglia, whereas microbleeds can be missed by overlap of veins or the hypointense appearance of ferritin-containing basal ganglia on the 1.5T scan or on the TE2 of the 7T scan. 25 Previous studies comparing the detection of microbleeds at 3T and 1.5T found significantly more microbleeds at 3T. In addition, the microbleed conspicuity improved at 3T.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The use of the TE1 image at 7T is helpful to distinguish microbleeds from deoxyhemoglobin in veins and ferritin in the basal ganglia, whereas microbleeds can be missed by overlap of veins or the hypointense appearance of ferritin-containing basal ganglia on the 1.5T scan or on the TE2 of the 7T scan. 25 Previous studies comparing the detection of microbleeds at 3T and 1.5T found significantly more microbleeds at 3T. In addition, the microbleed conspicuity improved at 3T.…”
Section: Discussionmentioning
confidence: 86%
“…Recently, we showed that the TE1 image provides a good contrast of the dark microbleeds against a homogeneous, more hyperintense signal intensity of the brain tissue and that 85% of all microbleeds are visible on the TE1 image. 25 If a microbleed is visible on the TE1 image and also shows a blooming effect on the TE2, it is more easily classified Fig 2. A, On this 1.5T scan, a hypointense lesion (arrow ) is visible that is not a typical well-defined, round-shaped lesion as in the definition of a microbleed. This lesion was not scored as a microbleed on the 1.5T scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 On 7T dual-echo T2*-weighted MR imaging, for example, up to 3 times as many microbleeds can be detected than on 1.5T MR images. 2 However, susceptibility effects of other structures also complicate microbleed detection at higher field strengths.…”
mentioning
confidence: 98%
“…2 However, susceptibility effects of other structures also complicate microbleed detection at higher field strengths. 1 We sought to determine mIP processing conditions with an optimal balance between accuracy and rating time and to determine intra-and interrater agreement for these processing conditions on 7T MR imaging.…”
mentioning
confidence: 99%